2007
DOI: 10.1002/jbm.b.30954
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of silicone‐hydrogel contact lenses surfaces before and after wear using atomic force microscopy

Abstract: The present study suggests that surface treatment of silicone-hydrogel contact lenses can play a role in the prevention of a significant increase in roughness, and contribute to the better clinical tolerance of these lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 16 publications
4
32
2
Order By: Relevance
“…R a and R q seem to be the most helpful and consistent to characterize surface topography of the spun membranes. R max can be affected by local imperfections or sample contamination leading to higher values than expected and so material characterization based on this parameter could be unreliable [39]. The pure PVDF membrane presented the smoothest and its surface was covered with a multitude of small peak (R a = 10.73 nm and R q = 13.45 nm for inner surface, R a = 16.66 nm and R q = 21.06 nm for outer surface).…”
Section: Membrane Surface Analysismentioning
confidence: 98%
“…R a and R q seem to be the most helpful and consistent to characterize surface topography of the spun membranes. R max can be affected by local imperfections or sample contamination leading to higher values than expected and so material characterization based on this parameter could be unreliable [39]. The pure PVDF membrane presented the smoothest and its surface was covered with a multitude of small peak (R a = 10.73 nm and R q = 13.45 nm for inner surface, R a = 16.66 nm and R q = 21.06 nm for outer surface).…”
Section: Membrane Surface Analysismentioning
confidence: 98%
“…Gonzalez-Meijome et al [10] studied several Si-H materials, shown in Table 1, and concluded that Balafilcon A presents a more irregular surface, probably due to the plasma oxidation treatment used to improve wettability, having Galyfilcon A and Lotrafilcon A the smother surface. Lira et al [13] studied three different Si-H materials (see Table 1) and also observed that Galyfilcon has the smother surface meanwhile Balafilcon A has the more irregular one. Guryca et al [12] studied several Si-H and hydrogel materials and obtained that the surface roughness depends on the technique used to fabricate the CLs.…”
Section: Introductionmentioning
confidence: 97%
“…The Atomic Force Microscopy (AFM) is a technique that becomes useful to determine these properties, as was pointed out in an earlier work by Rabke et al [1]. Consequently, several authors [2][3][4][5][6][7][8][9][10][11][12][13][14][15] performed studies on CLs and using the AFM technique, but none of them used the Peak Force Quantitative Nanomechanics mode to determine the nanomechanical properties, such as the adhesion or the Young modulus, also named elastic modulus.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters generally used to quantify roughness include height parameters such as average roughness (Ra), mean-square-roughness (Rms) and Maximum Roughness (Rmax) (Baguet et al, 1993;Guryca et al, 2007;Bhatia et al, 1997;Hinojosa Rivera and Reyes Melo, 2001;Lira et al, 2008;Gonzalez-Meijome et al, 2009;Giraldez et al, 2010a;Giraldez et al, 2010c;Gonzalez-Meijome et al, 2006a). Ra is the average deviation or arithmetic mean of the profile from the mean line; it is universally accepted and is the most used international parameter of roughness.…”
Section: Height Parametersmentioning
confidence: 99%
“…Atomic force microscopy (AFM) provides detailed information on the surface characteristics of contact lenses (Bhatia et al, 1997;Baguet et al, 1993;Baguet et al, 1995;Bruinsma et al, 2003;Lira et al, 2008;Guryca et al, 2007;Gonzalez-Meijome et al, 2006a;Gonzalez-Meijome et al, 2009;Teichroeb et al, 2008;Maldonado-Codina and Efron, 2005) and is a powerful tool for the high resolution examination of the structure of the hydrated contact lens surface. The method has the advantages that it avoids artefacts due to dehydration and coating (Bhatia et al, 1997;Kim et al, 2002), and allows for non-destructive surface topography and roughness measurements.…”
Section: Atomic Force Microscopymentioning
confidence: 99%